Durlobactam, a New Diazabicyclooctane β-Lactamase Inhibitor for the Treatment of Acinetobacter Infections in Combination With Sulbactam - Shapiro, Adam B.; Moussa, Samir H.; McLeod, Sarah M.; Durand-Réville, Thomas; Miller, Alita A. (Frontiers in Microbiology, 2021)
Durlobactam is a new member of the diazabicyclooctane (DBO) class of β-lactamase inhibitors with broad spectrum activity against Ambler class A, C and D serine β-lactamases. Sulbactam is a first generation β-lactamase inhibitor with activity limited to a subset of class A enzymes that also has direct-acting antibacterial activity against Acinetobacter spp. The latter feature is due to sulbactam’s ability to inhibit certain penicillin-binding proteins (PBPs), essential enzymes involved in bacterial cell wall synthesis in this pathogen. Because sulbactam is also susceptible to cleavage by numerous β-lactamases, its clinical utility for the treatment of contemporary Acinetobacter infections is quite limited. However, when combined with durlobactam, the activity of sulbactam is effectively restored against these notoriously multidrug-resistant strains. This combination of sulbactam-durlobactam is currently in late-stage development for the treatment of Acinectobacter infections, including those caused by carbapenem-resistant isolates, for which there is a high unmet medical need. The following mini-review summarizes the molecular drivers of efficacy of this combination against this troublesome pathogen, with an emphasis on the biochemical features of each partner.